Atrioventricular Node Slow‐Pathway Ablation Reduces Atrial Fibrillation Inducibility: A Neuronal Mechanism. Issue 6 (10th June 2016) - Yin, Xiaomeng; Xi, Yutao; Zhang, Shulong; Xia, Yunlong; Gao, Lianjun; Liu, Jinqiu; Cheng, Nancy; Chen, Qi; Cheng, Jie; Yang, Yanzong
Abstract : Background: Radiofrequency ablation (RFA) for atrioventricular nodal reentrant tachycardia appears to reduce atrial tachycardia, which might relate to parasympathetic denervation at cardiac ganglionated plexuses. Methods and Results: Compared to 7 control canines without RFA, in 14 canines, RFA at the bottom of Koch's triangle attenuated vagal stimulation–induced effective refractory periods prolongation in atrioventricular nodal and discontinuous atrioventricular conduction curves but had no effect on the sinoatrial node. RFA attenuated vagal stimulation–induced atrial effective refractory periods shortening and vulnerability window of atrial fibrillation widening in the inferior right atrium and proximal coronary sinus but not in the high right atrium and distal coronary sinus. Moreover, RFA anatomically impaired the epicardial ganglionated plexuses at the inferior vena cava‒inferior left atrial junction. This method was also investigated in 42 patients who had undergone ablation of atrioventricular nodal reentrant tachycardia, or 12 with an accessory pathway (AP) at the posterior septum (AP‐PS), and 34 patients who had an AP at the free wall as control. In patients with atrioventricular nodal reentrant tachycardia and AP‐PS, RFA at the bottom of Koch's triangle prolonged atrial effective refractory periods and reduced vulnerability windows of atrial fibrillation widening at the inferior right atrium, distal coronary sinus and proximal coronary sinus but not the high right atrium. In patients with AP‐free wall, RFA had no significant atrial effects. Conclusions: RFA at the bottom of Koch's triangle attenuated local autonomic innervation in the atrioventricular node and atria, decreased vagal stimulation–induced discontinuous atrioventricular nodal conduction, and reduced atrial fibrillation inducibility due to impaired ganglionated plexuses. In patients with atrioventricular nodal reentrant tachycardia or AP‐PS, RFA prolonged atrial effective refractory periods, and narrowed vulnerability windows of atrial fibrillation.